Statistical Provision of the Management of the Higher Education Quality in Ukraine - Gerasymenko, S.; Gerasymenko, V.; Chupryna, O. (Taras Shevchenko National University of Kyiv, 2015)
The article deals with the problem of statistical estimation of the quality of teaching in the higher educational establishment and the quality of grounding graduating seniors. This is due to the necessity to realize practically the clauses of the new law of Ukraine "About the higher education". The necessity to estimate the quality of the higher education in Ukraine using the basic statistical approaches and methods which are used in the management of the quality of goods and services is substantiated.

Розглянуто проблему статистичного оцінювання якості освітньої діяльності вищих навчальних закладів та якості підготовки їх випускників, у зв'язку з необхідністю впровадження в практику положень нового Закону України "Про вищу освіту". Обґрунтовано необхідність оцінювання якості вищої освіти в Україні із застосуванням базових статистичних підходів та методів, використовуваних в управлінні якістю товарів і послуг.
Статистичне забезпечення управління якістю вищої освіти в Україні
Keywords: higher educational establishment; higher education; quality; quality of higher education; standard; criterion; the law; ranking; the market of educational services; statistical approaches and methods; вищий навчальний заклад; вища освіта; якість; якість вищої освіти; стандарт; критерій; статистичне оцінювання